Neurodevelopmental Outcomes of Neonatal Rotavirus-Associated Leukoencephalopathy - Cho, Jae Young; Yeom, Jung Sook; Kim, Young-Soo; Choi, Dae-Seob; Park, Ji Sook; Park, Eun Sil; Seo, Ji-Hyun; Lim, Jae-Young; Woo, Hyang-Ok; Park, Chan-Hoo (Neuropediatrics, 2022)
Rotavirus infection has been reported to be associated with neonatal seizures with a diffuse and symmetrical diffusion restriction of periventricular white matter, namely, neonatal rotavirus-associated leukoencephalopathy. The extensive white matter injury seen in this cohort raises concerns about the long-term neurodevelopmental outcomes. In the present study, we prospectively assessed the neurodevelopmental outcomes of 13 patients with neonatal rotavirus-associated leukoencephalopathy at a median age of 26 months (range, 23–68 months). Neurodevelopmental outcomes were evaluated using a neurological examination, developmental evaluations, and magnetic resonance imaging (MRI) of the brain. Overall, 6 of the 13 patients (46%) had abnormal neurodevelopmental outcomes: 1 patient had mental retardation, visual–motor integration (VMI) dysfunction, cerebral palsy, and epilepsy; 1 patient had cerebral palsy and VMI dysfunction; remaining 4 patients had VMI dysfunction. Follow-up MRI in 12 of 13 patients showed an increased signal intensity on periventricular white matter in all patients. These findings suggested that neonatal rotavirus-associated leukoencephalopathy could not be assumed to be benign in long-term neurodevelopment, particularly in VMI function. Early intervention and long-term follow-up are necessary for these patients. Our findings raise caution for rotavirus infection in this vulnerable population for infants.
Keywords: rotavirus; leukoencephalopathy; infant; seizures; prognosis